Design and analysis of hexagonal antenna for UHF RFID reader - Nasrun Afiq, Adnan; Mohd Hisyam, Mohd Ariff; Noor Zirwatul Ahlam, Naharuddin; Mohammad Fadhil, Abas; Mohd Mawardi, Saari; Rahimah, Jusoh (AIP Publishing, 2025)
The purpose of this paper is to present a design and analysis of hexagonal antenna for Ultra High Frequency (UHF) Radio Frequency Identification (RFID) Reader Application, to embrace the benefits offered by UHF RFID systems. In this design the FR-4 material is used to have medium, low cost and lightweight structure. The proposed antenna made up of hexagonal antenna patch and rectangular shape for the substrate. The antenna is meant to work on a frequency range of 919 MHz to 923 MHz, which is reserved for Malaysia's UHF RFID system. A voltage standing wave ratio (VSWR) of 1.14 and a gain of 5.87 at 921 MHz was obtained in CST microwave studio. The result of antenna parameter such as bandwidth, return loss and radiation pattern also discussed.